Bioaccumulation and metabolism of polybrominated diphenyl ethers (PBDEs) in coenobitid hermit crabs from marine litter-polluted beaches in remote islands. (May 2023) - Tanaka, Nana; Takada, Naohiko; Takahashi, Mami; Yeo, Bee Geok; Oya, Yuki; Watanabe, Izumi; Fujita, Yoshihisa; Takada, Hideshige; Mizukawa, Kaoruko
Abstract: Plastic litter containing additives is potentially a major source of chemical contamination in remote areas. We investigated polybrominated diphenyl ethers (PBDEs) and microplastics in crustaceans and sand from beaches with high and low litter volumes on remote islands that were relatively free of other anthropogenic contaminants. Significant numbers of microplastics in the digestive tracts, and sporadically higher concentrations of rare congeners of PBDEs in the hepatopancreases were observed in coenobitid hermit crabs from the polluted beaches than in those from the control beaches. PBDEs and microplastics were detected in high amounts in one contaminated beach sand sample, but not in other beaches. Using BDE209 exposure experiments, similar debrominated products of BDE209 in field samples were detected in the hermit crabs. The results showed that when hermit crabs ingest microplastics containing BDE209, BDE209 leaches out and migrates to other tissues where it is metabolized. Graphical abstract: Unlabelled Image Highlights: PBDEs and microplastics in crustaceans on remote but littered beaches were analyzed. Microplastics were detected in the gut of hermit crabs from contaminated beaches. Many kinds of unusual PBDEs were also detected in hermit crab tissue. Exposure experiments revealed these congeners to be metabolites of BDE209.